Patient blood management for liver resection: consensus statements using Delphi methodology. Issue 4 (April 2019) - ,; Asai, Kengo; Barkun, Jeffrey; Bertens, Kimberley; Chaudhury, Prosanto; Cleary, Sean; Hogan, Michael; Jalink, Diderick; Law, Calvin; Livingstone, Scott; McGilvray, Ian; Metrakos, Peter; et al.
Abstract: Background: Blood loss and transfusion remain a significant concern in liver resection (LR). Patient blood management (PBM) programs reduce use of transfusions and improve outcomes and costs, but are not standardized for LR. This study sought to create an expert consensus statement on PBM for LR using modified Delphi methodology. Methods: An expert panel representing hepato-biliary surgery, anesthesiology, and transfusion medicine was invited to participate. 28 statements addressing the 3 pillars of PBM were created. Panelists were asked to rate statements on a 7-point Likert scale. Three-rounds of iterative rating and feedback were completed anonymously, followed by an in-person meeting. Consensus was reached with at least 70% agreement. Results: The 35 experts panel recommended routine pre-operative transfusion risk assessment, and investigation and management of anemia with iron supplementation. Intra-operatively, restrictive fluid administration without routine central line insertion was recommended, along with intermittent hepatic pedicle occlusion and surgical techniques considerations. Specific criteria for restrictive intra-operative and post-operative transfusion strategy were recommended. Conclusions: PBM for LR included medical and technical interventions throughout the perioperative continuum, addressing specificities of LR. Diffusion and adoption of these recommendations can standardize PBM for LR to improve patient outcomes and resource utilization.